Aspiration of Tri-folded, Endothelium-In Grafts for Descemet Membrane Endothelial Keratoplasty. Issue 5 (May 2019) - Karakus, Sezen; Ighani, Mehrnaz; Noparat, Puntakarn; Tofigh, Marjan; Chiang, Eric; Barnes, Kali; Chen, Conan Y.; Liu, Tiffany S.; Eghrari, Allen O.
Abstract : Purpose: In Descemet membrane endothelial keratoplasty (DMEK), loading and positioning of tri-folded grafts into a cartridge is generally conducted with forceps or a hook, risking graft tear or trauma. We demonstrate the feasibility of loading tri-folded grafts into a cartridge with no touch to the endothelium required beyond the tri-folding process. Methods: A corneoscleral rim with a prestripped DMEK graft is placed into a petri dish. After the graft is tri-folded with forceps and removed from its stromal attachment, the graft is gently wicked into the tip of a saline-filled Alcon B IOL cartridge connected to IV extension tubing and a 3 cc syringe, drawn into the cartridge by positioning it adjacent to the graft tip. The remainder of the graft is aspirated with the addition of saline. The cartridge orientation is reversed for graft injection. In this retrospective analysis, we analyzed surgical videos for preparation times, and assessed postoperative visual acuity, pachymetry, and endothelial cell density. Results: Thirteen cases underwent this approach. Median preparation time from stain to cartridge eye contact was 8.5 minutes, and time from graft injection to final centration and bubbling was 2.9 minutes. Corneal thickness decreased from a median of 623 microns preoperatively to 566 μm at 1 month ( P = 0.038). Visual acuity improved by 1 month by a median of 0.3 logarithm of the minimum angle of resolution (logMAR) ( P = 0.016). Endothelial cell density decreased by 32.4% at 1 month compared with baseline. Conclusions: Endothelium-in DMEK grafts may be loaded into a plastic cartridge using a skill set similar to aspiration of a scroll. Abstract : Supplemental Digital Content is Available in the Text.